E-mail Communication in the Management of Gastroenterology Patients: A Review - Ian Plener; Andrew Hayward; Fred Saibil (Canadian Journal of Gastroenterology and Hepatology)
E-mail correspondence between physicians and patients can be a useful tool to improve communication efficiency, provide economic and ecological benefits, improve therapeutic interventions and adherence, and enhance self-management. The model of self-management in chronic disease has become an integral component of North American and British medicine. From a practical standpoint, the use of e-mail between physicians and patients can complement the self-management model.